Phosphorus-containing (METH)acryloyl composition and method for producing the same
A composition of multiple phosphorus-containing (meth)acryloyl compounds with different structures addresses halogen-free flame retardancy and dielectric challenges, ensuring stable and uniform properties in resin compositions for electronic devices.
Patent Information
- Application Number
- JP2023102312
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-22
- Publication Date
- 2025-01-09
AI Technical Summary
Existing resin compositions used in electronic devices face challenges with halogen-free flame retardancy, difficulty in impregnation due to phosphorus-containing compound precipitation, and uneven distribution, while also requiring low dielectric constant and dielectric loss tangent for high-speed communication.
A composition of two or more types of phosphorus-containing (meth)acryloyl compounds with different chemical structures is developed, preventing precipitation and ensuring excellent solvent dissolution stability, flame retardancy, and maintaining uniform properties during impregnation and coating.
The composition achieves stable flame retardancy with low dielectric constant and dielectric loss tangent, allowing uniform impregnation and maintaining properties, even during coating on sheets, resulting in a cured product with improved heat resistance.
Smart Images

Figure 2025002261000034 
Figure 2025002261000035 
Figure 2025002261000036
Abstract
Description
[Technical field]
[0001] The present invention relates to a phosphorus-containing (meth)acryloyl compound which exhibits flame retardancy and is excellent in solvent solubility stability, and which is suitably used as a reactive flame retardant. [Background technology]
[0002] Resin compositions for use in electronic devices, particularly circuit boards, need to be made flame retardant. However, due to safety concerns about the halides generated during combustion and the history of fatal accidents caused by the smoke generated, it is desirable to make flame retardants halogen-free. For example, Patent Document 1 discloses a resin composition that has been imparted flame retardancy by a resin containing phosphorus atoms.
[0003] Furthermore, as a halogen-free flame retardant, there is an increasing demand for reactive flame retardants because they do not cause the drawbacks of additive-type flame retardants, such as environmental pollution due to bleed-out and elution, or a decrease in glass transition temperature due to plasticization.
[0004] On the other hand, in order to improve high-speed communication technology, resin compositions are required to have low dielectric constants and low dielectric loss tangents, and there is a shift from epoxy resins, which have been the mainstream in circuit board applications, to resins having radically polymerizable functional groups, such as maleimide resins and vinyl resins as disclosed in Patent Documents 2 and 3.
[0005] It is also necessary to impart halogen-free flame retardancy to maleimide resins and vinyl resins, and for example, Patent Document 4 discloses a phosphorus-containing vinylbenzyl ether compound obtained by reacting a specific phosphorus-containing phenolic compound with a vinylbenzyl halide, and Non-Patent Document 1 discloses a polyfunctional (meth)acryloyl compound using an adduct of DOPO and quinones. However, when impregnating glass cloth, there is a problem that the phosphorus-containing compound in the resin composition dissolved in the solvent precipitates, making impregnation difficult or causing uneven distribution of the resin with high flame retardancy.
[0006] For these reasons, there is a demand for reactive flame retardants that have a radically polymerizable functional group and are halogen-free, exhibit a low dielectric constant and a low dielectric loss tangent, and also have excellent solvent solubility stability. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 11-279258 [Patent Document 2] JP 2017-137492 A [Patent Document 3] JP 2004-123873 A [Patent Document 4] JP 2020-147519 A [Non-patent literature]
[0008] [Non-Patent Document 1] Ind. Eng. Chem. Res. 2013, 52, 12855-12864 Summary of the Invention [Problem to be solved by the invention]
[0009] The problem to be solved by the present invention is to provide a composition of a phosphorus-containing (meth)acryloyl compound which can impart halogen-free flame retardancy, has low dielectric constant and low dielectric tangent, and at the same time, has excellent solvent solubility, is less likely to precipitate, and has dramatically improved stability. [Means for solving the problem]
[0010] As a result of extensive research aimed at solving the above-mentioned problems, the inventors have discovered that by mixing two or more phosphorus-containing (meth)acryloyl compounds having different structures into a composition, precipitation (crystallization) from a solvent dissolution can be dramatically suppressed, and the composition also has excellent flame retardancy, heat resistance, and dielectric properties, which has led to the present invention.
[0011] That is, the present invention provides A composition of phosphorus-containing (meth)acryloyl compounds represented by general formula (1), characterized in that the composition contains at least two phosphorus-containing (meth)acryloyl compounds having different chemical structures. [ka] (In general formula (1), R1, R2, and R3 are independently hydrogen, a hydroxyl group, or a group represented by -R, where R is a hydrocarbon group having 1 to 40 carbon atoms. R1 and R2 may be the same or different and may form a cyclic structure together with the phosphorus atom. n is 0 or 1. X is an aromatic hydrocarbon group having 6 to 20 carbon atoms, and m is 1 to 3.)
[0012] The present invention provides a method for producing a phosphorus-containing composition, which comprises reacting at least two or more hydroxyl-containing phosphorus compounds represented by general formula (2) with (meth)acrylic acid, (meth)acrylic anhydride, or a halogenated (meth)acryloyl compound to (meth)acryloylate the two or more hydroxyl-containing phosphorus compounds. [ka] (In general formula (2), R1, R2, X, n, and m are the same as those in general formula (1).) The present invention is a method for producing a phosphorus-containing (meth)acryloyl composition according to claim 3, characterized in that a phosphorus-containing compound represented by general formula (3) is reacted with a quinone compound to obtain two or more kinds of hydroxyl group-containing phosphorus compounds, and then the obtained two or more kinds of hydroxyl group-containing phosphorus compounds are (meth)acryloylated. [ka] (In general formula (3), R1, R2, and n are the same as those in general formula (1).)
[0013] The present invention relates to a flame-retardant resin composition obtained by blending a phosphorus-containing (meth)acryloyl composition with one or more thermosetting resins or thermoplastic resins; a prepreg obtained by blending the flame-retardant resin composition with a fibrous substrate and semi-curing the composition; or a resin sheet obtained by applying the flame-retardant resin composition to a resin film and semi-curing the composition; a cured product obtained by curing the flame-retardant resin composition, prepreg, or resin sheet; and a laminate for electronic circuit boards containing the flame-retardant resin composition as an essential component. Effect of the Invention
[0014] The phosphorus-containing (meth)acryloyl composition of the present invention has two or more different structures, and therefore is stable when dissolved in a solvent, does not precipitate during the preparation process, and maintains uniform properties even when impregnated into a substrate such as a glass cloth or applied to a sheet, thereby achieving stable flame retardancy. The resulting cured product exhibits a low dielectric constant, dielectric tangent, and excellent heat resistance. [Brief description of the drawings]
[0015] [Figure 1] 3 shows an HPLC chart of the phosphorus-containing methacryloyl compound obtained in Example 2. [Diagram 2] 3 shows an HPLC chart of the phosphorus-containing methacryloyl compound obtained in Example 6. [Diagram 3] 3 shows an HPLC chart of the phosphorus-containing methacryloyl compound obtained in Example 7. [Figure 4] 4 shows an HPLC chart of the phosphorus-containing methacryloyl compound obtained in Example 8. [Diagram 5] 3 shows an HPLC chart of the phosphorus-containing methacryloyl compound obtained in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention will be described in detail below. In explaining the present invention, with regard to the names of acrylic resins, acrylic compounds, acrylate compounds, etc., in accordance with common practice, for example, both "acryloyl" and "methacryloyl" may be collectively referred to as "(meth)acryloyl", both "acrylic" and "methacrylic" may be collectively referred to as "(meth)acrylic", and both "acrylate" and "methacrylate" may be collectively referred to as "(meth)acrylate".
[0017] The phosphorus-containing (meth)acryloyl composition of the present invention is a composition of phosphorus-containing (meth)acryloyl compounds represented by general formula (1), and is characterized by containing at least two types of phosphorus-containing (meth)acryloyl compounds having different chemical structures. [ka] The phosphorus-containing (meth)acryloyl composition of the present invention contains at least two phosphorus-containing (meth)acryloyl compounds having different chemical structures, and by containing each compound in an amount of 1 area % or more, the solvent solubility is improved. The content of each compound is more preferably 10 area % or more, and even more preferably 15 area % or more. The content (area %) of each component can be measured by high performance liquid chromatography (HPLC). In the case of a two-component system containing two components with different chemical structures, each component is preferably contained in the range of 30 area % to 70 area %, more preferably 40 area % to 60 area %. In the case of a ternary system containing three components with different chemical structures, each component is preferably contained in the range of 10 area % to 60 area %, more preferably 15 area % to 50 area %. In the case of a four-component system containing four components with different chemical structures, each component is preferably contained in an amount of 10 area % to 50 area %, more preferably 10 area % to 45 area %. When five or more components with different chemical structures are included, each component is preferably contained in an amount of 1 area % to 50 area %, more preferably 1 area % to 40 area %. Here, R1 and R2 are preferably phenyl groups, and may have an alkyl group or a phenyl group having 1 to 6 carbon atoms as a substituent. R3 is preferably an alkyl group having 1 to 3 carbon atoms. X is a group derived from a quinone compound, and is preferably an aromatic ring group such as benzene, toluene, xylene, or naphthalene, and each aromatic ring may have an alkyl group or a phenyl group having 1 to 6 carbon atoms as a substituent. The same applies to the following formulae. The phosphorus-containing (meth)acryloyl composition of the present invention preferably has a phosphorus content of 1 to 20% by weight, more preferably 3 to 10% by weight, based on the solid content.
[0018] The hydroxyl group-containing phosphorus compound represented by the general formula (2) can be synthesized by reacting an organic phosphorus compound having an active hydrogen directly bonded to a phosphorus atom with a quinone compound by a known method as disclosed in JP-A-61-236787, JP-A-05-331179, JP-A-05-39345, etc. Examples of the organic phosphorus compound include dimethylphosphine, diethylphosphine, diphenylphosphine, etc.; examples of the phosphine oxides include dimethylphosphine oxide, diethylphosphine oxide, diphenylphosphine oxide, menthylphenylphosphinate, tert-butylphenylphosphine oxide, etc.; examples of the phosphoric acid esters include diethylhydrogenphosphite, bis(2-ethylhexyl)hydrogenphosphite, dilaurylhydrogenphosphite, dioleylhydrogenphosphite, diphenylhydrogenphosphite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (HCA, manufactured by Sanko Co., Ltd.), 8-benzyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (Bz-HCA, manufactured by Sanko Co., Ltd.), etc.; however, the present invention is not limited to these, and two or more kinds may be used. Specific examples of quinone compounds include 1,4-benzoquinone, 1,2-benzoquinone, toluquinone, phenylbenzoquinone, 1,4-naphthoquinone, 1,2-naphthoquinone, hydroxynaphthoquinone, methylnaphthoquinone, etc. These quinones may be used alone or in combination of two or more kinds, and are not limited to these. [ka]
[0019] It is important to use two or more hydroxyl-containing phosphorus compounds having different chemical structures in combination as represented by the general formula (2). Although it is possible to combine multiple different single compounds, it is also possible to obtain a mixture of two or more hydroxyl-containing phosphorus compounds by selecting an organophosphorus compound and a quinone compound represented by the general formula (3). [ka] For example, when toluquinone is used as the quinone compound, isomers in which the methyl groups are located at the ortho, para, and meta positions are obtained, so that a mixture of two or more types can be easily obtained, thereby improving the solvent solubility. The reaction between the organic phosphorus compound and the quinone compound is carried out by dissolving the organic phosphorus compound in an inert solvent and adding the quinone compound. The molar ratio of the quinone compound to the organophosphorus compound is preferably in the range of 1.2 to 0.7 mol, more preferably in the range of 1.0 to 0.9 mol.
[0020] The hydroxyl-containing phosphorus compound represented by general formula (2) can be synthesized by reacting an organic phosphorus compound having an active hydrogen bonded directly to the phosphorus atom represented by general formula (3) with a quinone compound. This reaction may result in the by-product of a structure in which two phosphorus atoms are added to a quinone compound represented by the following general formula (4). However, this is not a compound that impedes the effects of the present invention, and there is no problem if it is included. [ka]
[0021] The hydroxyl group-containing phosphorus compound represented by the above general formula (2) may be a commercially available product, such as diphenylphosphinyl hydroquinone (PPQ, manufactured by Hokko Chemical Industry Co., Ltd.), 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide (HCA-HQ, manufactured by Sanko Co., Ltd.), 10-(2,5-dihydroxynaphthyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide (HCA-NQ, manufactured by Sanko Co., Ltd.), 1,4-cyclooctylenephosphonyl hydroquinone, and 1,5-cyclooctylenephosphonyl hydroquinone (CPHO-HQ, manufactured by Nippon Chemical Industry Co., Ltd.), which may be combined to produce two or more types of hydroxyl group-containing phosphorus compounds.
[0022] The reaction of a hydroxyl group-containing phosphorus compound with (meth)acrylic acid, a (meth)acryloyl halide or (meth)acrylic anhydride is not particularly limited and can be carried out in the same manner as in a normal (meth)acryloylation reaction of an alcohol compound or a phenol compound.
[0023] By using multiple types of (meth)acrylic acid, (meth)acryloyl halide, or (meth)acrylic anhydride for the (meth)acryloylation reaction, it is possible to obtain a phosphorus-containing (meth)acryloyl composition containing two or more different chemical structures as the phosphorus-containing (meth)acryloyl compound represented by general formula (1). For example, when (meth)acrylic acid is used, it can be produced by condensation reaction of a hydroxyl group-containing phosphorus compound with 1 to 10 times the amount of (meth)acrylic acid relative to the hydroxyl groups in the presence of a strong acid catalyst such as sulfuric acid, p-toluenesulfonic acid, methanesulfonic acid, etc. This reaction needs to proceed while removing the by-product condensation water from the system, so a hydrocarbon solvent that forms an azeotrope with water, such as toluene, is used as the reaction solvent, and the reaction solution is heated to about 70 to 140°C.
[0024] In addition, the phosphorus-containing (meth)acryloyl compound of the present invention can be obtained by reacting a hydroxyl group-containing phosphorus compound with a (meth)acryloyl halide or (meth)acrylic anhydride. Examples of the (meth)acryloyl halide that can be used include acryloyl fluoride, acryloyl chloride, acryloyl bromide, acryloyl iodide and other acryloyl halides, methacryloyl fluoride, methacryloyl chloride, methacryloyl bromide, methacryloyl iodide, methylene butanoyl chloride, methylene pentanoyl chloride, methylene hexanoyl chloride, methylene cyclohexane acetyl chloride, methylene benzene acetyl chloride and other methacryloyl halides.
[0025] In the practice of the present invention, one or a mixture of two or more of the (meth)acryloyl halide and (meth)acrylic anhydride may be used. In the present invention, it is preferable to use (meth)acrylic chloride and / or (meth)acrylic anhydride, because they are easily available.
[0026] The amount of the (meth)acryloyl halide and / or (meth)acrylic anhydride used is 0.8-5 mol, preferably 0.95-4 mol, per mol of hydroxyl group of the phosphorus-containing phenol compound used as a raw material. If the amount of the (meth)acrylic halide and / or (meth)acrylic anhydride used is less than the above range, the heat resistance of the obtained phosphorus-containing (meth)acryloyl compound decreases, and the amount of residual hydroxyl groups increases, which deteriorates the dielectric properties, which is not preferable, whereas if the amount used is more than the above range, the efficiency of the reactor decreases, which increases the cost, which is not preferable.
[0027] When using a (meth)acryloyl halide, hydrogen halide corresponding to the (meth)acrylic acid halide used is generated as a by-product, so it is preferable to use a basic compound in combination to trap the generated hydrogen halide while carrying out the reaction. The basic compound is not particularly limited, and examples thereof include aliphatic amines such as trimethylamine, triethylamine, diisopropylethylamine, tri-n-propylamine, triisopropylamine, tributylamine, N-methyl-diethylamine, N-ethyl-dimethylamine, and N-ethyl-diamylamine; aromatic amines such as N,N-dimethylaniline and diethylaniline; alicyclic amines such as N,N-dimethyl-cyclohexylamine and N,N-diethyl-cyclohexylamine; heterocyclic amines such as N,N-dimethylaminopyridine, N-methylmorpholine, diazabicycloundecene (DBU), diazabicyclononene (DBN), N-methylpyridine, N-methylpyrrolidine, and N-methylimidazole; and diamines such as tetramethylethylenediamine and triethylenediamine. In particular, aliphatic amines such as trimethylamine and triethylamine, and pyridine are preferred because of their easy availability.
[0028] The amount of the basic compound used is, for example, 0.8 to 7 moles, preferably about 0.95 to 5 moles, relative to 1 mole of hydroxyl group of the phosphorus-containing phenol compound used as a raw material. If the amount of the tertiary amine used is less than the above range, the hydrogen halide cannot be completely trapped, and corrosion of the reaction apparatus occurs, whereas if it exceeds the above range, the cost tends to be high.
[0029] When the reaction is carried out with (meth)acrylic anhydride, a catalyst may not be used, but when the reaction is difficult to proceed, an ester catalyst, an acid catalyst, a base catalyst, or a Lewis acid catalyst can be used. Here, examples of the ester catalyst include alkali metal salts of lower carboxylic acids such as sodium, potassium, etc., such as sodium acetate, potassium propionate, and sodium (meth)acrylate. Examples of the acid catalyst include inorganic acids such as sulfuric acid and boric acid; and organic acids such as methanesulfonic acid and paratoluenesulfonic acid. Examples of the base catalyst include organic bases such as nitrogen-containing aliphatic compounds such as triethylamine and triethylenediamine, and nitrogen-containing aromatic heterocyclic compounds such as pyridine, 4-(dimethylamino)pyridine, and N-methylimidazole. Examples of the Lewis acid catalyst include aluminum chloride and zinc chloride.
[0030] The amount of catalyst used is preferably 10% or less, more preferably 5% or less, based on the amount of (meth)acrylic anhydride used. If the amount of catalyst used exceeds the above range, it takes a long time to remove the catalyst and the catalyst is likely to remain in the product, resulting in deterioration of characteristics.
[0031] In the reaction of hydroxyl group-containing phosphorus compound with (meth)acryloyl halide or / and (meth)acrylic anhydride, it is preferable to use an organic solvent as a reaction solvent and carry out the reaction in solution. The solvent that can be used is not particularly limited as long as it is not reactive with phenol compound and (meth)acrylic acid halide or / and (meth)acrylic anhydride, and includes tetrahydrofuran, dioxane, ethyl acetate, acetonitrile, benzene, toluene, xylene, dichloromethane, chloroform, carbon tetrachloride, dimethylformamide, dimethylacetamide, dimethylsulfoxide, hexamethylphosphoric acid triamide, water, etc., and these can be used in combination as necessary.
[0032] In the reaction of the hydroxyl group-containing phosphorus compound with the (meth)acrylic acid halide and / or (meth)acrylic acid anhydride, the reaction temperature is preferably −50 to 150° C., and since a polymerization reaction is likely to occur if the reaction is carried out at a high temperature, the reaction temperature is more preferably −25 to 100° C. The reaction time is appropriately set according to the set reaction temperature, and is preferably set in the range of 1 to 48 hours.
[0033] The reaction of the hydroxyl group-containing phosphorus compound with (meth)acrylic acid, (meth)acryloyl halide or (meth)acrylic anhydride may be carried out in the presence of a polymerization inhibitor. By adding a polymerization inhibitor, it is possible to prevent the (meth)acrylic acid, (meth)acryloyl halide or (meth)acrylic anhydride to be reacted, or the (meth)acrylic acid ester as the target product from polymerizing to produce an oligomer as a by-product. As the polymerization inhibitor, known ones can be used without limitation, and examples thereof include organic compounds such as hydroquinone, hydroxymonomethyl ether, t-butylcatechol, t-butylhydroquinone, 4-methoxyphenol, 4-methoxy-1-naphthol, and phenothiazine, as well as copper compounds such as copper chloride and copper sulfide, and these may be used in combination.
[0034] After completion of this reaction, the resulting reaction liquid (reaction mixture) may be subjected to, if necessary, distillation of the reaction solvent, solvent replacement, etc., and purified using means such as washing with water, activated carbon treatment, and silica gel chromatography, to obtain the desired (meth)acryloyl compound of the present invention.
[0035] Next, a flame-retardant resin composition containing the phosphorus-containing (meth)acryloyl composition of the present invention as an essential component and mixed with a curable resin or a thermoplastic resin will be described.
[0036] In the flame-retardant resin composition of the present invention, the blending ratio is not particularly limited, but for example, 10 to 300 parts by weight of the phosphorus-containing (meth)acryloyl composition may be blended per 100 parts by weight of the total amount of the curable resin and the thermoplastic resin, preferably 20 to 200 parts by weight, more preferably 50 to 150 parts by weight.
[0037] Examples of the curable resin include unsaturated polyester resin, curable maleimide resin, epoxy resin, polycyanate resin, phenol resin, and one or more vinyl compounds having one or more polymerizable unsaturated hydrocarbon groups in the molecule. Preferred are epoxy resin and one or more vinyl compounds having one or more polymerizable unsaturated hydrocarbon groups in the molecule.
[0038] When the curable resin is an epoxy resin, it is preferable that the curable resin is one or more epoxy resins selected from epoxy resins having two or more epoxy groups in one molecule. Examples of such epoxy resins include cresol novolac type epoxy resins, triphenylmethane type epoxy resins, biphenyl epoxy resins, naphthalene type epoxy resins, bisphenol A type epoxy resins, and bisphenol F type epoxy resins. These may be used alone or in combination of two or more. It is believed that the use of such epoxy resins can minimize the influence on the excellent dielectric properties and fluidity of the curable resin composition of the present invention, and can sufficiently increase the heat resistance and adhesion of the cured product.
[0039] In addition, when an epoxy resin is contained, a curing agent may be used in addition to the epoxy resin. The curing agent is not particularly limited, and examples thereof include phenol-based curing agents, amine-based compounds, amide-based compounds, acid anhydride-based compounds, naphthol-based curing agents, active ester-based curing agents, benzoxazine-based curing agents, and cyanate ester-based curing agents. These may be used alone or in combination of two or more.
[0040] Furthermore, when an epoxy resin is blended, a curing accelerator can be used as necessary. For example, amines, imidazoles, organic phosphines, Lewis acids, etc. The amount added is usually in the range of 0.2 to 5 parts by weight per 100 parts by weight of the epoxy resin.
[0041] When the curable resin is one or more vinyl compounds having one or more polymerizable unsaturated hydrocarbon groups in the molecule (hereinafter also referred to as vinyl compounds), the type is not particularly limited. That is, the vinyl compounds may be any compounds that can be crosslinked and cured by reacting with the phosphorus-containing (meth)acryloyl compound of the present invention. More preferably, the polymerizable unsaturated hydrocarbon group is a carbon-carbon unsaturated double bond, and more preferably, a compound having two or more carbon-carbon unsaturated double bonds in the molecule.
[0042] The average number of carbon-carbon unsaturated double bonds (the number of vinyl groups (including substituted vinyl groups); also referred to as the number of terminal double bonds) per molecule of the vinyl compounds as the curable resin varies depending on the Mw of the vinyl compounds, but is preferably, for example, 1 to 20, and more preferably 2 to 18. If the number of terminal double bonds is too small, it tends to be difficult to obtain a cured product with sufficient heat resistance. On the other hand, if the number of terminal double bonds is too large, the reactivity becomes too high, and problems such as reduced storage stability of the curable resin composition or reduced flowability of the curable resin composition may occur.
[0043] Examples of the vinyl compounds include trialkenyl isocyanurate compounds such as triallyl isocyanurate (TAIC), modified polyphenylene ethers (PPE) whose ends are modified with (meth)acryloyl groups or styryl groups, polyfunctional (meth)acrylate compounds having two or more (meth)acryloyl groups in the molecule, vinyl compounds (polyfunctional vinyl compounds) having two or more vinyl groups in the molecule such as polybutadiene, and vinylbenzyl compounds such as styrene and divinylbenzene. Among these, compounds having two or more carbon-carbon double bonds in the molecule are preferred, and specific examples include TAIC, polyfunctional (meth)acrylate compounds, modified PPE resins, polyfunctional vinyl compounds, and divinylbenzene compounds. It is believed that the use of these compounds allows crosslinking to be more suitably formed by the curing reaction, and the heat resistance of the cured product of the curable resin composition can be further improved. These compounds may be used alone or in combination of two or more. Compounds having one carbon-carbon unsaturated double bond in the molecule may also be used in combination. An example of a compound having one carbon-carbon unsaturated double bond in the molecule is a compound having one vinyl group in the molecule (monovinyl compound).
[0044] Examples of the thermoplastic resin include polystyrene, polyphenylene ether resin, polyetherimide resin, polyethersulfone resin, PPS resin, polycyclopentadiene resin, polycycloolefin resin, etc., known thermoplastic elastomers (e.g., styrene-ethylene-propylene copolymer, styrene-ethylene-butylene copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, hydrogenated styrene-butadiene copolymer, hydrogenated styrene-isoprene copolymer, etc.), and rubbers (e.g., polybutadiene, polyisoprene).Preferably, unmodified or modified polyphenylene ether resin and hydrogenated styrene-butadiene copolymer can be mentioned.
[0045] The flame-retardant resin composition of the present invention may contain a radical polymerization initiator (polymerization catalyst or crosslinking agent) that generates radicals by light and / or heat. Examples of the photopolymerization initiator include benzoins such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, and benzoin isobutyl ether; acetophenones such as acetophenone, 2,2-diethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 2-hydroxy-2-methyl-phenylpropan-1-one, diethoxyacetophenone, 1-hydroxycyclohexyl phenyl ketone, and 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one; 2-ethylanthraquinone, 2-tertiary butyric acid, and the like. Examples of suitable thioxanthones include anthraquinones such as 2,4-diethylthioxanthone, 2-chloroanthraquinone, and 2-amyl anthraquinone; thioxanthones such as 2,4-diethylthioxanthone, 2-isopropylthioxanthone, and 2-chlorothioxanthone; ketals such as acetophenone dimethyl ketal and benzyl dimethyl ketal; benzophenones such as benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide and 4,4'-bismethylaminobenzophenone; and phosphine oxides such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide.Examples of thermal radical initiators include, but are not limited to, peroxides such as benzoyl peroxide, cumene hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, di-t-butyl peroxide, t-butylcumyl peroxide, 1,3-bis(butylperoxyisopropyl)benzene, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, dicumyl peroxide, di-t-butylperoxyisophthalate, t-butylperoxybenzoate, 2,2-bis(t-butylperoxy)butane, 2,2-bis(t-butylperoxy)octane, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, di(trimethylsilyl)peroxide, and trimethylsilyltriphenylsilylperoxide. Although not a peroxide, 2,3-dimethyl-2,3-diphenylbutane can also be used as a radical polymerization initiator. However, the radical polymerization initiator is not limited to these examples, and two or more radical initiators may be used in combination. The amount of the radical polymerization initiator to be added is preferably 0.01 to 10 parts by weight, and more preferably 0.1 to 5 parts by weight, based on 100 parts by weight of the resin component.
[0046] The flame-retardant resin composition of the present invention essentially contains a phosphorus-containing (meth)acryloyl composition having two or more different chemical structures represented by general formula (1) as a reactive flame retardant, and the phosphorus content in the flame-retardant resin composition is preferably 0.5 to 5.0% by weight, more preferably 1.0 to 4.0% by weight.
[0047] The flame-retardant resin composition of the present invention can be blended with a filler. Examples of fillers include those added to enhance heat resistance and flame retardancy, and known fillers can be used, but are not particularly limited. In addition, by including a filler, heat resistance, dimensional stability, flame retardancy, and the like can be further improved. Specific examples include silica such as spherical silica, metal oxides such as alumina, titanium oxide, and mica, metal hydroxides such as aluminum hydroxide and magnesium hydroxide, talc, aluminum borate, barium sulfate, and calcium carbonate. When a metal hydroxide such as aluminum hydroxide or magnesium hydroxide is used, it acts as a flame retardant assistant, and flame retardancy can be ensured even if the phosphorus content is low. Among these, silica, mica, and talc are preferred, and spherical silica is more preferred. In addition, one of these may be used alone, or two or more may be used in combination.
[0048] The filler may be used as it is, or may be surface-treated with a silane coupling agent such as an epoxysilane type or an aminosilane type. As the silane coupling agent, vinylsilane type, methacryloxysilane type, acryloxysilane type, and styrylsilane type silane coupling agents are preferred from the viewpoint of reactivity with the radical polymerization initiator. This increases the adhesive strength with the metal foil and the interlayer adhesive strength between resins. In addition, the filler may be used by adding the silane coupling agent by integral blending, instead of surface-treating the filler in advance.
[0049] The content of the filler is preferably 10 to 200 parts by mass, and more preferably 30 to 150 parts by mass, per 100 parts by mass of the total of solid contents excluding the filler (including organic components such as monomers and flame retardants, but excluding solvents).
[0050] The flame-retardant resin composition of the present invention may further contain additives other than those described above, such as antifoaming agents such as silicone-based antifoaming agents and acrylic acid ester-based antifoaming agents, heat stabilizers, antistatic agents, ultraviolet absorbers, dyes and pigments, lubricants, dispersants such as wetting dispersants, and the like.
[0051] The cured product obtained by curing the flame-retardant resin composition of the present invention can be used as a molded product, a laminate, a casting, an adhesive, a coating, or a film. For example, the cured product of a semiconductor encapsulation material is a casting or molding, and the method for obtaining the cured product for such use is to cast the curable resin composition or mold it using a transfer molding machine, an injection molding machine, or the like, and further heat it at 80 to 230°C for 0.5 to 10 hours to obtain the cured product.
[0052] The flame-retardant resin composition of the present invention can also be used as a prepreg. When producing a prepreg, the composition can be prepared in a varnish form to be used for impregnating a substrate (fibrous substrate) for forming a prepreg, or for use as a circuit board material for forming a circuit board, and can be used as a varnish for circuit board materials. Specific examples of the uses of the circuit board material include printed wiring boards, printed circuit boards, flexible printed wiring boards, and build-up wiring boards.
[0053] The organic solvent used in the resin varnish is not particularly limited as long as it does not inhibit the curing reaction. For example, ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; esters such as ethyl acetate, propyl acetate, and butyl acetate; polar solvents such as dimethylacetamide and dimethylformamide; aromatic hydrocarbon solvents such as toluene and xylene, and the like can be used alone or in combination of two or more. From the viewpoint of dielectric properties, aromatic hydrocarbons such as benzene, toluene, and xylene are preferred.
[0054] When preparing the resin varnish, the amount of the organic solvent used is preferably 5 to 900 parts by weight, more preferably 10 to 700 parts by weight, and particularly preferably 20 to 500 parts by weight, relative to 100 parts by weight of the curable resin composition of the present invention.
[0055] The substrate used to prepare the prepreg may be a known material, such as glass fiber, carbon fiber, polyester fiber, polyamide fiber, alumina fiber, or paper, which may be used alone or in combination of two or more. If necessary, a coupling agent may be used in these substrates to improve the adhesiveness at the interface between the resin and the substrate. As the coupling agent, a silane coupling agent, a titanate coupling agent, an aluminum-based coupling agent, a zircoaluminate coupling agent, or other common coupling agents may be used.
[0056] A method for obtaining a prepreg includes a method in which the resin varnish is impregnated into a substrate and then dried. The impregnation is performed by dipping, coating, or the like. The impregnation can be repeated multiple times as necessary, and in this case, it is also possible to repeat the impregnation using multiple solutions with different compositions and concentrations to adjust the final resin composition and resin amount to the desired amount. After the impregnation, the prepreg can be obtained by heating and drying at 100 to 180°C for 1 to 30 minutes. Here, the amount of resin in the prepreg is preferably 30 to 80% by weight.
[0057] The curable resin composition of the present invention can also be used as a laminate. When a laminate is formed using a prepreg, one or more prepregs are laminated, and a metal foil is placed on one or both sides to form a laminate, which is then heated and pressed to be integrated. Here, as the metal foil, a single metal foil, an alloy metal foil, or a composite metal foil of copper, aluminum, brass, nickel, or the like can be used. The conditions for heating and pressing the laminate may be appropriately adjusted so that the curable resin composition is cured, but if the pressure is too low, air bubbles may remain inside the obtained laminate, resulting in a decrease in electrical properties, so it is preferable to pressurize under conditions that satisfy moldability. For example, the temperature is 180 to 250°C, and the pressure is 49.0 to 490 N / cm 2 (5~50kgf / cm 2), and the heating and pressing time can be set to 40 to 240 minutes. Furthermore, a multilayer board can be produced by using the single-layer laminate thus obtained as an inner layer material. In this case, a circuit is first formed on the laminate by an additive method, a subtractive method, or the like, and the surface of the formed circuit is treated with an acid solution for blackening to obtain an inner layer material. An insulating layer is formed on one or both circuit-forming surfaces of this inner layer material by a resin sheet, a metal foil with resin, or a prepreg, and a conductor layer is formed on the surface of the insulating layer to produce a multilayer board.
[0058] The curable composition of the present invention can also be used for a build-up film. For example, a method for producing a build-up film from the resin composition of the present invention includes a method of applying the above-mentioned resin varnish onto a support film and drying it to form a film-like insulating layer. The film-like insulating layer thus formed can be used as a build-up film for a multilayer printed wiring board. EXAMPLES
[0059] The present invention will now be described with reference to examples, but is not limited to these. In each example, all parts are by weight. The physical properties in the synthesis examples and examples were measured by the methods shown below. (1) Phosphorus content: Sulfuric acid, hydrochloric acid, and perchloric acid were added to the sample, which was then heated and wet-ashed to convert all phosphorus atoms into orthophosphate. Metavanadate and molybdate were reacted in the sulfuric acid acid solution, and the absorbance of the resulting phosphorus vanadate molybdate complex was measured at 420 nm. The phosphorus atom content was calculated using a calibration curve prepared in advance using potassium dihydrogen phosphate and expressed as a percentage. (2) Solvent solubility: In a varnish adjusted to a solid content of 50% by mass using toluene as the solvent, those that showed no precipitation after one week were rated as ◯, and those that showed precipitation were rated as ×. Those that did not produce a methacryloyl compound were marked as -. (3) Glass transition temperature: Measured from the baseline shift using differential scanning calorimetry at a heating rate of 10° C. / min. (4) Dielectric constant and dielectric loss tangent: The dielectric constant and dielectric loss tangent at a frequency of 10 GHz were determined by the SPDR method using a material analyzer (manufactured by AGILENT Technologies) in accordance with the IPC-TM-6502.5.5.9 standard. (5) Flame retardancy: Evaluated by the vertical method in accordance with UL94. The evaluation was recorded as V-0, V-1, or V-2. (6) HPLC (High Performance Liquid Chromatography): Using 0.5% phosphoric acid aqueous solution and acetonitrile as eluents, the acetonitrile was gradient from 40% to 100% in 30 minutes, and the measurement was performed with a Shimadzu LC-20A at a flow rate of 1.0 ml. The detector was a photodiode array detector, and the peaks of each component were detected at a wavelength of 210 nanometers. The column temperature was 40°C, and the Imtakt Cadenza CD-C18 column was used.
[0060] (Synthesis Example 1) 340 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 660 parts of toluene were charged into a glass separable flask equipped with a stirrer, a thermometer, a cooling tube, and a nitrogen gas inlet device, and dissolved at 80 ° C. 245 parts of 1,4-naphthoquinone were added in portions while paying attention to the reaction heat. The reaction was continued, and the temperature was raised to 110 ° C. for further reaction. After 3 hours, a slurry solution was obtained in which dark brown crystals were precipitated. The crystals were separated by filtration and dispersed in 500 parts of methanol. This operation was performed three times, and then the mixture was dried in a hot air circulating oven to obtain a light yellow powder of phosphorus-containing phenolic compound 10-(2,5-dihydroxynaphthyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-NQ). [ka]
[0061] (Synthesis Example 2) The same operation as in Synthesis Example 1 was carried out using the same apparatus as in Synthesis Example 1, except that 320 parts of diphenylphosphine oxide was used instead of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, to obtain a light yellow powder of a phosphorus-containing phenol compound, 2-diphenylphosphinyl-1,4-naphthalene diol (DPO-NQ). [ka]
[0062] (Synthesis Example 3) Using the same apparatus as in Synthesis Example 2, the same operation as in Synthesis Example 1 was carried out except that 189 parts of toluquinone was used instead of 1,4-naphthoquinone, to obtain a light yellow powder of a phosphorus-containing phenol compound, diphenylphosphinyl-methylbenzenediol (DPO-TQ). [ka]
[0063] Example 1 Into a separable flask equipped with a stirrer, a nitrogen inlet tube, a reflux condenser, and a thermometer, 25 parts of 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (product name HCA-HQ, Sanko Co., Ltd.) as a hydroxyl group-containing phosphorus compound and 25 parts of DOPO-NQ obtained in Synthesis Example 1, [ka] 50 parts of toluene was charged as a solvent and dispersed. 2 parts of 4-dimethylaminopyridine (manufactured by Tokyo Chemical Industry Co., Ltd.) and 32 parts of triethylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) were added. 52 parts of methacrylic anhydride, [ka] The reaction was carried out by dropping the compound. The reaction was monitored by HPLC to confirm the disappearance of the raw material peak and the completion of methacryloylation, after which the triethylamine was removed under reduced pressure and 1 part of methanol was added to decompose the remaining methacrylic anhydride. Methacrylic acid and methyl methacrylate were removed by washing with water, and the mixture was dehydrated, filtered and concentrated to obtain a 50% non-volatile toluene solution. The obtained methacryloyl compound was two components, with the methacrylate of HCA-HQ and the methacrylate of DOPO-NQ being 44.6 to 55.4 in terms of area percentage. The phosphorus content was 6.0% relative to the solid content. There was no precipitation in the obtained varnish.
[0064] Example 2 Using the same apparatus as in Example 1, 25 parts of DPO-NQ obtained in Synthesis Example 2, 25 parts of DOPO-NQ obtained in Synthesis Example 1, and [ka] The same procedure was repeated except that 53 parts of methacrylic anhydride was used, and a 50% non-volatile toluene solution was obtained. The HPLC chart is shown in Figure 1. The obtained methacryloyl compound was two components, with the area % ratio of DPO-NQ methacrylate and DOPO-NQ methacrylate being 50.6:49.4. The phosphorus content was 6.1% relative to the solid content. No precipitation occurred in the obtained varnish.
[0065] Example 3 Using the same apparatus as in Example 1, 48 parts of DPO-TQ obtained in Synthesis Example 3 as a hydroxyl group-containing phosphorus compound, [ka] The same procedure was carried out except that 70 parts of toluene and 103 parts of methacrylic anhydride were used to obtain a toluene solution with a non-volatile content of 50%. The obtained methacryloyl compound was the three components of the methacrylate isomers of DPO-TQ, and in the order from left to right in the above structural formula, the area % ratio was 17.3:46.9:35.8. The phosphorus content was 6.8% relative to the solid content. There was no precipitation in the obtained varnish.
[0066] Example 4 Using the same apparatus as in Example 1, 13 parts of diphenylphosphine oxide (DPO) and 13 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (product name HCA by Sanko Co., Ltd.) were used as phosphorus-containing compounds. [ka] 61 parts of toluene was charged and dissolved by heating. 18 parts of 1,4-naphthoquinone (Naphthoquinone: NQ, manufactured by Air Water Performance Chemical Inc.) [ka] While being careful of heat generation, the reaction was carried out to obtain two types of hydroxyl-containing phosphorus compounds. Next, the same operation was carried out except that 1.6 parts of 4-dimethylaminopyridine, 26 parts of triethylamine, and 41 parts of methacrylic anhydride were used, to obtain a toluene solution with a non-volatile content of 50%. The obtained methacryloyl compound was two components, with the methacrylate of DPO-NQ and the methacrylate of HCA-NQ being 53.8 to 46.2 in terms of area percentage. The phosphorus content was 6.4% relative to the solid content. There was no precipitation in the obtained varnish.
[0067] Example 5 Using the same apparatus as in Example 1, 26 parts of HCA as a phosphorus-containing compound and 61 parts of toluene were charged and dissolved. 14.4 parts of toluquinone (TQ) were added and reacted to obtain two types of hydroxyl group-containing phosphorus compounds. [ka] Next, a similar operation was carried out except that 1.6 parts of 4-dimethylaminopyridine, 26 parts of triethylamine, and 41 parts of methacrylic anhydride were used to obtain a 50% non-volatile toluene solution. The obtained methacryloyl compound was two components of methacrylate isomers of HCA-TQ, and in the order from left to right in the structural formula below, the area % ratio was 57.9 to 42.1. The phosphorus content was 6.6% relative to the solid content. There was no precipitation in the obtained varnish. [ka]
[0068] Example 6 Using the same apparatus as in Example 1, 30 parts of diphenylphosphine oxide (DPO) as a phosphorus-containing compound and 70 parts of toluene were charged and dissolved. 17.8 parts of toluquinone (TQ) were added and reacted to obtain three types of hydroxyl group-containing phosphorus compounds. [ka] Next, the same procedure was carried out except that 2.0 parts of 4-dimethylaminopyridine, 33 parts of triethylamine, and 103 parts of methacrylic anhydride were used to obtain a 50% non-volatile toluene solution. The HPLC chart is shown in Figure 2. The obtained methacryloyl compound was the three components of the methacrylate isomers of DPO-TQ, and in the order from left to right in the above structural formula, the area % ratio was 16.7:47.2:36.1. The phosphorus content was 6.7% relative to the solid content. No precipitation occurred in the obtained varnish.
[0069] Example 7 Using the same apparatus as in Example 1, 26 parts of diphenylphosphine oxide (DPO) as a phosphorus-containing compound, [ka] 61 parts of toluene were charged and dissolved. 2 parts of 1,4-naphthoquinone (NQ), 13.8 parts of toluquinone (TQ), [ka] The reaction was carried out by adding 2.0 parts of 4-dimethylaminopyridine, 28 parts of triethylamine, and 45 parts of methacrylic anhydride, and the same procedure was carried out to obtain a 50% non-volatile toluene solution. The HPLC chart is shown in Figure 3. The obtained methacryloyl compound was four components, including the methacrylate isomers of DPO-NQ and DPO-TQ, and the area percentage ratio was 14.2:42.4:30.3:13.1 in the order from the top left to the bottom right of the structural formula below. The phosphorus content was 6.9% relative to the solid content. There was no precipitation in the obtained varnish. [ka]
[0070] Example 8 Using the same apparatus as in Example 1, 8 parts of HCA and 16 parts of diphenylphosphine oxide (DPO) as phosphorus-containing compounds, [ka] 56 parts of toluene were charged and dissolved. 13.9 parts of toluquinone (TQ), [ka] The reaction was carried out by adding 2.0 parts of 4-dimethylaminopyridine, 26 parts of triethylamine, and 40 parts of methacrylic anhydride, and the same procedure was carried out to obtain a 50% non-volatile toluene solution. The HPLC chart is shown in Figure 4. The obtained methacryloyl compound was five components including the isomers of HCA-TQ methacrylate and DPO-TQ methacrylate, and the area percentage ratio was 10.9:38.3:29.6:1.3:19.8 in the order from the top left to the bottom right of the structural formula below. The phosphorus content was 6.7% relative to the solid content. There was no precipitation in the obtained varnish. The structural formula of the obtained methacryloyl resin is shown below. [ka]
[0071] Comparative Example 1 Using the same apparatus as in Example 1, 50 parts of HCA-HQ as a hydroxyl group-containing phosphorus compound was charged and dispersed in 50 parts of toluene. The same operation was carried out except that 2.2 parts of 4-dimethylaminopyridine, 34 parts of triethylamine, and 55 parts of methacrylic anhydride were used, but when washing water was charged, precipitation occurred and separation was not possible, and no methacryloyl compound was obtained.
[0072] Comparative Example 2 Using the same apparatus as in Example 1, the same operation was carried out except that 50 parts of DOPO-NQ of Synthesis Example 1, 50 parts of toluene, 2.0 parts of 4-dimethylaminopyridine, 27 parts of triethylamine, and 53 parts of methacrylic anhydride were used as the hydroxyl group-containing phosphorus compound, to obtain a toluene solution with a non-volatile content of 50%. The HPLC chart is shown in Figure 5. The obtained methacryloyl compound was one component. Precipitation was observed from the varnish the next day. The solid content was separated by filtration and dried. The phosphorus content of the obtained solid was 6.0%.
[0073] Comparative Example 3 Using the same apparatus as in Example 1, 50 parts of DPO-NQ of Synthesis Example 2 as a hydroxyl group-containing phosphorus compound and 50 parts of toluene were charged and dissolved. Dispersed. The same operation was carried out except that 2.0 parts of 4-dimethylaminopyridine, 31 parts of triethylamine, and 50 parts of methacrylic anhydride were used, but when washing water was charged, precipitation occurred and separation was not possible, and no methacryloyl compound was obtained.
[0074] Comparative Example 4 Using the same apparatus as in Example 1, 26 parts of Bz-HCA (Sanko Co., Ltd.) as a phosphorus-containing compound and 83 parts of toluene were charged and dissolved. 13.6 parts of 1,4-naphthoquinone were added and reacted to obtain one type of hydroxyl group-containing phosphorus compound Bz-HCA-NQ. Next, the same operation was performed except that 1.2 parts of 4-dimethylaminopyridine, 19 parts of triethylamine, and 29.4 parts of methacrylic anhydride were used to obtain a toluene solution with a non-volatile content of 50%. The obtained methacryloyl compound was one component. The phosphorus content was 5.2% relative to the solid content. Precipitation was observed from the varnish the next day. [ka]
[0075] <Solubility test> The results of the solubility test of the 50% toluene solutions prepared in Examples 1 to 8 and Comparative Examples 1 to 4 are shown in Table 1. [Table 1]
[0076] Examples 9 to 16, Comparative Examples 5 to 7 <Preparation of Curable Resin Composition and Preparation of Cured Product> A varnish was prepared by mixing the various components in the ratios shown in Tables 2 and 3, and was applied to a polyethylene terephthalate resin film and dried in an oven at 130°C for 5 minutes to prepare a film of the resin composition. Next, the film was pulverized to separate it from the polyethylene terephthalate resin film, and a powder of the resin composition was obtained. Furthermore, this powder was sandwiched between a stainless steel mirror plate together with a spacer, and molded in a vacuum oven at 210°C for 90 minutes to obtain a cured sample. The glass transition temperature and dielectric properties were evaluated using the cured sample, and the results are shown in Tables 2 and 3.
[0077] [Table 2]
[0078] [Table 3]
[0079] <Creating flame retardant test pieces> A varnish was prepared by mixing the various components in the proportions shown in Tables 2 and 3. This resin varnish was then impregnated into a glass cloth (manufactured by Nitto Boseki Co., Ltd.; 7628 type; product number H258), which was then dried by heating at 130°C for 5 minutes to obtain a prepreg. Eight sheets of the obtained prepreg were laminated with copper foil (Mitsui Mining & Smelting Co., Ltd., 3EC-III, thickness 35 μm) on top and bottom, and vacuum pressed at 2 MPa under temperature conditions of 130 ° C × 15 minutes + 190 ° C × 80 minutes to obtain a 1.6 mm thick laminate. The copper foil was etched and cut to obtain a flame retardant test piece. The flame retardant test piece was used to evaluate the flame retardancy, and the results are shown in Tables 2 and 3. [Industrial Applicability]
[0080] The phosphorus-containing (meth)acryloyl composition of the present invention contains at least two phosphorus-containing (meth)acryloyl compounds with different chemical structures, and therefore has good solvent solubility and does not precipitate, and when impregnating a fiber substrate or forming a film, a material with a uniform composition can be obtained, thereby exhibiting stable physical properties. Furthermore, by simultaneously producing two or more phosphorus-containing (meth)acryloyl compounds, a desired phosphorus-containing (meth)acryloyl composition can be easily obtained without precipitation during the process.
Claims
1. A composition of phosphorus-containing (meth)acryloyl compounds represented by general formula (1), characterized in that the composition contains at least two phosphorus-containing (meth)acryloyl compounds having different chemical structures. 【Chemistry 1】 (In general formula (1), R1, R2, and R3 are independently hydrogen, a hydroxyl group, or a group represented by -R, where R is a hydrocarbon group having 1 to 40 carbon atoms. R1 and R2 may be the same or different and may form a cyclic structure together with the phosphorus atom. n is 0 or 1. X is an aromatic hydrocarbon group having 6 to 20 carbon atoms, and m is 1 to 3.)
2. The phosphorus-containing (meth)acryloyl composition according to claim 1, comprising at least two phosphorus-containing (meth)acryloyl compounds having different chemical structures in an amount of 1 area % or more each of the compounds.
3. The method for producing the phosphorus-containing (meth)acryloyl composition according to claim 1, characterized in that two or more kinds of hydroxyl-containing phosphorus compounds represented by general formula (2) are reacted with (meth)acrylic acid, (meth)acrylic anhydride, or a halogenated (meth)acryloyl compound to (meth)acryloylate the two or more kinds of hydroxyl-containing phosphorus compounds. 【Chemistry 2】 (R1, R2, X, n, and m in formula (2) are the same as those in formula (1).)
4. The method for producing a phosphorus-containing (meth)acryloyl composition according to claim 3, characterized in that the phosphorus-containing compound represented by the general formula (3) is reacted with a quinone compound to obtain two or more kinds of hydroxyl group-containing phosphorus compounds, and then the obtained two or more kinds of hydroxyl group-containing phosphorus compounds are (meth)acryloylated. 【Chemistry 3】 (R1, R2, and n in formula (3) are the same as those in formula (1).)
5. A flame-retardant resin composition comprising the phosphorus-containing (meth)acryloyl composition according to claim 1 and at least one thermosetting resin or thermoplastic resin.
6. A prepreg obtained by blending the flame-retardant resin composition according to claim 5 with a fibrous base material and semi-curing the blend.
7. A resin sheet obtained by applying the flame-retardant resin composition according to claim 5 to a resin film and semi-curing the composition.
8. A cured product obtained by curing the flame-retardant resin composition according to claim 5, the prepreg according to claim 6, or the resin sheet according to claim 7.
9. A laminate for electronic circuit boards, comprising the flame-retardant resin composition according to claim 5 as an essential component.
Citation Information
Patent Citations
Phosphorus-containing epoxy resin composition
JP1999279258A
Soluble, multifunctional vinyl aromatic copolymer and its polymerization process
JP2004123873A
Maleimide resin composition, prepreg and cured product thereof
JP2017137492A
Phosphorous-containing vinyl benzyl ether compound
JP2020147519A